2021
DOI: 10.1155/2021/9980410
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction of the Cancer Genome Atlas (TCGA) and Asian Cancer Research Group (ACRG) Gastric Cancer Molecular Classifications and Their Association with Clinicopathological Characteristics and Overall Survival in Moroccan Patients

Abstract: Introduction. The Cancer Genome Atlas (TCGA) project and Asian Cancer Research Group (ACRG) recently categorized gastric cancer into molecular subtypes. Nevertheless, these classification systems require high cost and sophisticated molecular technologies, preventing their widespread use in the clinic. This study is aimed to generating molecular subtypes of gastric cancer using techniques available in routine diagnostic practice in a series of Moroccan gastric cancer patients. In addition, we assessed the assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 38 publications
2
9
0
1
Order By: Relevance
“…In the ACRG study, more than 80% of the EMT cases were diffuse, but less than 50% of the diffuse-type cases belonged to the EMT subgroup [ 9 ]. The percentage of diffuse-type cases showing an EMT phenotype in our series (54%) was like the rate found in the ACRG study, as well as other reports [ 9 , 20 , 29 ]. In several studies, the Lauren classification was not used, and this did not allow a comparison with the present series [ 12 , 15 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the ACRG study, more than 80% of the EMT cases were diffuse, but less than 50% of the diffuse-type cases belonged to the EMT subgroup [ 9 ]. The percentage of diffuse-type cases showing an EMT phenotype in our series (54%) was like the rate found in the ACRG study, as well as other reports [ 9 , 20 , 29 ]. In several studies, the Lauren classification was not used, and this did not allow a comparison with the present series [ 12 , 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…Some reports have suggested that the EMT phenotype is correlated with younger age, diffuse/poorly differentiated histology, advanced TNM stage, and worse prognosis of GC [ 9 , 11 , 12 , 15 , 16 , 26 , 27 , 28 , 29 ]. The strong association with the diffuse histotype or undifferentiated histology may act as a confounding factor, and it is unclear if this association could explain the clinical behavior of EMT-positive tumors [ 9 , 12 , 28 , 29 ]. For this reason, we focused our analysis on MSS diffuse-type tumors.…”
Section: Discussionmentioning
confidence: 99%
“…We selected four datasets (GSE26901、GSE13861、GSE26899、GSE66229) about gene expression profiles of GC from GEO for the validation group. (GSE26901 from the Kosin University College of Medicine, GSE13861 from the Yonsei University Severance Hospital, GSE26899 from the Korea University Guro Hospital, and GSE66229 from the Asian Cancer Research Group) ( Cho et al, 2011 ; Oh et al, 2018 ; Nshizirungu et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned earlier, the most significant molecular systems published in GC are those of TCGA and the ACRG, which have been extensively analyzed in previous studies [ 74 , 149 , 150 , 151 , 152 , 153 , 154 ]. Nevertheless, various alternative classifications have emerged, either utilizing independent cohorts or drawing from existing databases, such as those of TCGA, the ACRG, or the Gene Expression Omnibus (GEO) repository.…”
Section: Molecular Classifications In Gastric Cancermentioning
confidence: 99%